Co-extinctions annihilate planetary life during extreme environmental change. Issue 1 (December 2018) - Strona, Giovanni; Bradshaw, Corey
Abstract Climate change and human activity are dooming species at an unprecedented rate via a plethora of direct and indirect, often synergic, mechanisms. Among these, primary extinctions driven by environmental change could be just the tip of an enormous extinction iceberg. As our understanding of the importance of ecological interactions in shaping ecosystem identity advances, it is becoming clearer how the disappearance of consumers following the depletion of their resources — a process known as 'co-extinction' — is more likely the major driver of biodiversity loss. Although the general relevance of co-extinctions is supported by a sound and robust theoretical background, the challenges in obtaining empirical information about ongoing (and past) co-extinction events complicate the assessment of their relative contributions to the rapid decline of species diversity even in well-known systems, let alone at the global scale. By subjecting a large set of virtual Earths to different trajectories of extreme environmental change (global heating and cooling), and by tracking species loss up to the complete annihilation of all life either accounting or not for co-extinction processes, we show how ecological dependencies amplify the direct effects of environmental change on the collapse of planetary diversity by up to ten times.